ANALISIS POTENSI PENGEMBANGAN SEKTOR PETERNAKAN BERBASIS PEMBERDAYAAN PEREMPUAN DI KABUPATEN BATANG - Meriwijaya; Luth (Halu Oleo University, 2022)
This study aims to determine the potential for developing livestock resources, especially land resources, human resources (HR) and the use of livestock technology in Batang Regency. The study used a qualitative descriptive approach. The results of this study indicate that the development of the livestock sector based on women's empowerment is very potential to be carried out in Batang Regency. This is evidenced by the existence of adequate carrying capacity, among others: First, 63,610.99 hectares or 80% of the total area of Batang Regency is used as agricultural land, indicating that the availability of feed ingredients derived from forage grass is very fulfilled so that the potential for developing livestock land is very open. . Second, the availability of female human resources which reached 401,328 people with 281,879 people included in the working age category and a total of 4,177 people in 2021 being female job seekers, indicating that female human resources in Batang Regency have the potential to be empowered in order to develop the livestock sector based on women's empowerment. Third, the use of livestock technology that is only limited to feed processing technology and temperature regulation technology in chicken farms opens opportunities and has the potential to be developed in the management of the livestock sector in Batang Regency in the future.